Understanding water governance in the Central Rift Valley of Ethiopia: governance framework, coherence and practices - Jibat, E.; Senbeta, F.; Zeleke, T.; Hagos, Fitsum (Springer, 2024)
Water governance demands multi-sector participation beyond the state; and, appropriate laws, policies, regulations, and institutions need to be developed and put in place for sustainable use of water resources. A good water policy, a critical and integral instrument of water governance, guides water use schemes and ensures equitable water distribution among users. The Ethiopian Central Rift Valley (CRV) is rich in water resources, but these water resources are currently under severe strain owing to an imbalance in human-water interactions. This study examined the state of water resources governance framework, policy coherence, actors’ engagement and transparency, accountability, and participation in irrigation water supply in the CRV of Ethiopia. Key informant interviews (KII), focused group discussions, and document reviews were used to gather data for the study. The NVivo 11 program was used to organize, code, and analyze the data. The results revealed that water resources governance practices such as water allocation and apportionment, water resources protection, and conservation activities were inappropriately exercised. Water resources management policy mechanisms were not fully put in place. Lack of coherence in water policy implementation, absence of clear roles and responsibilities of stakeholders, absence of transparency and accountability in irrigation water service delivery, and lack of meaningful participation of key actors in water governance decision-making were observed. As a result, over-abstraction, deterioration of buffer zone areas, and chemical erosion from surrounding farming are attributed to the reduction in water volume and quality in the CRV. These challenges have influenced aquatic ecosystem services and threaten the livelihoods of the surrounding communities. Hence, reforms relating to policy coherence and enforcement, stakeholder engagement, water distribution strategies, and the implementation of water governance principles must be given adequate emphasis.